Mangroves in Gujarat - Singh, H S (Gandhinagar, 2000)
Gujarat Ecological Education and Research (GEER) Foundation, Gandhinagar has prepared a comprehensive study report on Mangraves of Gujarat. Shri H. S. Singh, Director, GEER Foundation has produced a very informative report encompassing all the knowledge he had leamt from the fime he was Conservator of Marine National Park, Jamnagar till today.
Keywords: Mangroves-Gujarat